AVALIAÇÃO DA SEDE NO PÓS-OPERATÓRIO IMEDIATO EM PACIENTES SUBMETIDOS À ANESTESIA GERAL - DANTAS, Ana Beatriz Aparecida Fernandes; WATANABE, Elaine Aparecida Mye Takamatu; CARDOSO, Graziela Benites (ANAIS DO ENIC, 2025)
.